Tolerating Latency in Replicated State Machines Through Client Speculation - Wester, Benjamin; Cowling, James; Nightingale, Edmund B.; Chen, Peter M.; Flinn, Jason; Liskov, Barbara; Nightingale, Edmund B (The 6th USENIX Symposium on Networked Systems Design and Implementation (NSDI '09), 2009)
Replicated state machines are an important and widelystudied methodology for tolerating a wide range of faults. Unfortunately, while replicas should be distributed geographically for maximum fault tolerance, current replicated state machine protocols tend to magnify the effects of high network latencies caused by geographic distribution. In this paper, we examine how to use speculative execution at the clients of a replicated service to reduce the impact of network and protocol latency. We first give design principles for using client speculation with replicated services, such as generating early replies and prioritizing throughput over latency. We then describe a mechanism that allows speculative clients to make new requests through replica-resolved speculation and predicated writes. We implement a detailed case study that applies this approach to a standard Byzantine fault tolerant protocol (PBFT) for replicated NFS and counter services. Client speculation trades in 18% maximum throughput to decrease the effective latency under light workloads, letting us speed up run time on singleclient micro-benchmarks 1.08–19× when the client is co-located with the primary. On a macro-benchmark, reduced latency gives the client a speedup of up to 5×.